2018
DOI: 10.3389/fcell.2018.00106
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative CXXC Peptide Motif From Mesencephalic Astrocyte-Derived Neurotrophic Factor Antagonizes Programmed Cell Death

Abstract: Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a potent survival-promoting protein with neurorestorative effect for neurodegenerative diseases. Its mechanism of action, albeit poorly known, depends strongly on the CXXC motif (CKGC). Here we studied the survival-promoting properties of the CKGC tetrapeptide from MANF. In the Jurkat T lymphocytic cell line, CKGC potently inhibits death receptor Fas-induced apoptosis and mildly counteracts mitochondrial apoptosis and necroptosis. The peptide with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Whilst the antioxidant effects of the Trx system have been studied, the potential antioxidant properties of CXXC motifs in proteins outside of this system are less well understood. Recently, Cys to Ser site-directed mutagenesis of a CXXC motif in Mesencephalic Astrocyte-derived Neurotrophic Factor (MANF) demonstrated that the MANF CXXC motif provides protection from oxidative stress-induced apoptosis and reduces intracellular ROS [60]. This finding is similar to the data presented here and further supports an antioxidant role for the BCAT1 CXXC motif.…”
Section: Discussionsupporting
confidence: 87%
“…Whilst the antioxidant effects of the Trx system have been studied, the potential antioxidant properties of CXXC motifs in proteins outside of this system are less well understood. Recently, Cys to Ser site-directed mutagenesis of a CXXC motif in Mesencephalic Astrocyte-derived Neurotrophic Factor (MANF) demonstrated that the MANF CXXC motif provides protection from oxidative stress-induced apoptosis and reduces intracellular ROS [60]. This finding is similar to the data presented here and further supports an antioxidant role for the BCAT1 CXXC motif.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is speculated that CXXC motifs may be associated with metal binding or with isomerase activity and oxidative refolding [21,32]. More importantly, a recent study has shown that the CXXC motifs of MANF inhibited programmed cell death [31]. All in all, the above research indicates that CXXC motifs of MANF may play a significant role in promoting survival.…”
Section: Molecular Structurementioning
confidence: 95%
“…Furthermore, MANF contains two CXXC motifs, which are highly conserved and belongs to cysteine motifs. Cysteine motifs are usually critical for the enzymes participating in disulfide isomerization or redox reactions [31]. Therefore, it is speculated that CXXC motifs may be associated with metal binding or with isomerase activity and oxidative refolding [21,32].…”
Section: Molecular Structurementioning
confidence: 99%
“…It should be noted that MANF’s protective activity by gene therapy in vitro was abolished with the deletion of the C-terminal RTDL domain, but the protein was biologically active and showed protective effects on ischemic stroke in vivo . Thus, only the C-terminal CxxC is essential for the neuroprotective activity of MANF in ischemic stroke in vivo ( Matlik et al, 2015 ) and antagonizes cell death ( Božok et al, 2018 ).…”
Section: Mesencephalic Astrocyte-derived Neurotrophic Factormentioning
confidence: 99%